Analisis Kebutuhan Buku Ajar Kajian Ayat Memper Surat Al Baqoroh pada Pondok Pesantren as Salam Pasuruan - Nila Takrima; Siti Sulaikho (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The purpose of this study was to find out how much the students of the As-Salam Pasuruan Islamic Boarding School needed for textbooks on verse studies per letter al-Baqarah. The results of this analysis can later be used as a benchmark for how much the students at the As-Salam Pasuruan Islamic Boarding School need for the textbook for the study of verse per letter al-Baqarah. Research conducted is part of quantitative research. By taking a sample of 37 students out of 138. The highest percentage results were obtained from the questionnaire items 1 to 14, namely 8.43% (Highly Needed) on item 12. In the teaching and learning process of memorizing the holy Qur'an, teachers really need innovations which makes students easy and excited. So we need a reference book that is used by the teacher to make it easier for the students. Based on the results of the research on the needs of the As-Salam Pasuruan Islamic Boarding School students for textbooks on verse studies per letter al-Baqarah, it can be concluded that the students really need textbooks that contain and make it easy to learn verses deepen the Qur'an especially in surah al-Baqarah with a percentage value of 8.43% (Very Needed)